(untitled) (Forum Penelitian Agro Ekonomi, 2016)
From the agrarian politic history view, the eastern region of Indonesia has a relatively strong competition potential in the global arena. However, since the past five decades, the capacity of socio-economic-politic-culture of the eastern region of Indonesia was degraded to the lowest level. The political planning concern of the central government in the agrarian resource development management is the obstacle point to allow serious implication on social gap and backwardness. The agrarian politic set back in the western part of Indonesia has a heavy influence on the community’s socio-economic livelihood who are depending on local agrarian resources. The prominent ability of several local kings of kingdoms in the eastern Indonesia to perform agricultural trade at a global level during the period of 15-18 centuries has no longer existed. In the future, a strong political support is required to reform agrarian development planning for the eastern region of Indonesia. The plan should cover: First, the vision and direction to establish a strong, self-support, high competitive, fair, and sustainable industrial community based on the existing agrarian resource management. Second, to produce high value of agrarian products, manage by integrated organizations, use high technology and innovation, apply sharing system on collective assets, and select appropriate business adjusted to the existing local agro-ecosystems. Third, strengthen infrastructure networks, support financial institutions, and apply law enforcement in accordance with good governance in a decentralized government administration. Fourth, to establish the community’s rights to express their political opinion and aspiration, to involve in organization (economic, society, and politic), and support on local wisdom. Fifth, to perform policies that integrates agrarian management, safety and defense, and the empowerment of civil society in the eastern part of Indonesia.